Pengembangan Service Automation Application dengan Pendekatan Customer Self-Service (Studi Kasus: Martabak Djoeragan Pekanbaru) - Boby Chandra Panjaitan; Juni Nurma Sari; Anggy Trisnadoli (Universitas Islam Sumatera Utara, 2019)
In the industrial era 4.0, it has now provided automatic convenience in all aspects of the field, including the culinary business. Operationally customer relationship management has an application that is service automation, where this application is computerized technology to support service staff automatically. In service automation applications, there is software functionality offered, namely customer self-service with web customer service self-service. Martabak Djoeragan, which is a business in the culinary food field in terms of the number of sales of martabak, is very much classified. Based on transaction data in 2017 customer orders can reach more than 300 orders in a day wherein the service process Martabak Djoeragan uses a manual cash register system to serve each order, the cashier must serve one by one each customer order. Today, of course, in terms of the service aspects of the Martabak Djoeragan shop, it is necessary to have an automatic convenience in serving each customer order. The results of service automation applications that have been built based on black-box testing, UAT and Likert scales have been running according to user needs which resulted in applications that provide convenience in the field of serviceIn the industrial era 4.0, it has now provided automatic convenience in all aspects of the field, including the culinary business. Operationally customer relationship management has an application that is service automation, where this application is computerized technology to support service staff automatically. In service automation applications, there is software functionality offered, namely customer self-service with web customer service self-service. Martabak Djoeragan, which is a business in the culinary food field in terms of the number of sales of martabak, is very much classified. Based on transaction data in 2017 customer orders can reach more than 300 orders in a day wherein the service process Martabak Djoeragan uses a manual cash register system to serve each order, the cashier must serve one by one each customer order. Today, of course, in terms of the service aspects of the Martabak Djoeragan shop, it is necessary to have an automatic convenience in serving each customer order. The results of service automation applications that have been built based on black-box testing, UAT and Likert scales have been running according to user needs which resulted in applications that provide convenience in the field of service